Ekonomiczne uwarunkowania ekologizacji polskiego rolnictwa w aspekcie dostosowań do członkostwa w UE - Kociszewska, Irena; Kociszewski, Karol (The Economic Conditions of Polish Agriculture Ecologization in the Aspect of Adjustments to Membership in EU, 2005)
In the context of integration process, environment protection in agriculture is one of many areas of necessary adjustments to EU requirements. There are good conditions in Poland to introduce EU legal regulations (the structure of farmland, the size of average farm, methods of production) - especially organic farming, agri-environment and afforestation measures. It could result in both economic and ecologie profits. Polish legal regulation (except agri-environment measures and executive enactments) is almost adjusted to EU requirements, but there is no proper strategy to accomplish the regulation in practice - it is very expensive. The directions of the adjustments should be an introduction of agri-environment programs in a wide range what would enable the participation in Guarantee and Guidance Section of EAGGF fund and the multifunctional development of rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 116-128